Karakteristik Minuman Sari Jeruk Keprok Terigas dengan Penambahan beberapa Jenis Penstabil - Imro’ah Ikarini; Trifena Honestin; Hasim Ashari; Zainuri Hanif (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Ikarini I, Honestin T, Ashari H, Hanif Z, 2020. Karakteristik Minuman Sari Jeruk Keprok Terigas dengan Penambahan beberapa Jenis Penstabil. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Postharvest technology is needed so that the abundant citrus fruits at harvest time can be utilized and at the same time can increase the added value of these oranges. The potential to increase the added value of Indonesian citrus products is still huge. The processing of oranges into fruit juice drinks can be one way to increase the added value of oranges. Orange juice is currently a trendy drink as it contains vitamin C, which increases the human body's immunity in the pandemic era. The study aims to determine the effects of several types of stabilizers addition with several formulations on the physical and chemical characteristics, as well as sensory properties of the panellists' preference for Keprok Terigas juice. This study made use of Completely Randomized Design (CRD) with two factors, the first factor was the type of stabilizer (CMC, xanthan gum, arabic gum) and the second factor was the concentration of the stabilizer (0.025%, 0.05%, 0.075%, 0.1%). Results of the study indicated that vitamin C contained in the citrus fruit juice ranged from 13.49 to 24.69 mg/100 grams. Citrus fruit juice had a total dissolved solid value of 11.10 -12.63, pH was 3.535-3.787, total acid was 4.567-7.433 and viscosity value of 4.167-43.500 cp. The treatment of several types of stabilizers affected the value of vitamin C content, viscosity, and total dissolved solids, yet it gave no affect on the pH of the citrus juice.